Semiotika Dakwah tentang Toleransi dalam Video Film Animasi Culapculip - Silvianti Silvianti; Moh. Amiruddin (Lembaga Pengembangan Kinerja Dosen, 2025)
Currently, preaching is no longer limited to being present in a gathering or discussion room directly, but can also be delivered through daring or digital media that has developed rapidly. Preaching through sosial media such as YouTube, Instagram, TikTok, for example, is often done in cartoon films. The purpose of this studi is to determine the meaning of denotation, connotation also a myth in the animated film CulapCulip. By using Roland Barthes' semiotic theory to analyze or describe the meaning contained in the animated images, the researcher used a descriptive qualitative method. The data collection method used by the researcher was by recording also watching the animated film CulapCulip with the theme of tolerance. The results of this studi indicate that the most appropriate analysis theory to apply in studying a film is Roland Barthes' semiotics. With the aim that the meaning contained in each scene can be easily understood related to the use of denotation, connotation, also myth in the animated film CulapCulip. The researcher studied six scenes including the story of offerings, kicking, until shaking hands to prove it.